(untitled) (Texas Journal of Agriculture and Biological Sciences, 2022)
Many studies have shown that globalization has caused environmental pollution, carbon emission, climate change, increasing energy demand and inadequate natural resources. The application of passive design, which is part of sustainability, needs to give more attention in buildings. However, courtyard as a passive design strategy, use as a microclimate modifier is adopted in this study. Field measurement and Numerical Simulations using Envi-met V4.3 and Rayman Pro software were used as a methods to conduct this study. Three courtyard strategies, A (6m x 6m x 6m), B (15m x 7.5m x 7.5) and C (15m x 15m x 15), in the proportion of concrete, grass and trees were proposed to study their effect on the energy consumption and the thermal comfort by measuring the air temperature, mean radiant temperature and physiological equivalent temperature factors. . The results demonstrate that the courtyard strategy C that has the combination of trees and grass performed better with a reduction in air temperature of 0.9°C, 9.93°C reduction in Mean Radiant Temperature (Tmrt) and 19.40°C reduction in Physiological Equivalent Temperature (PET). The best strategy is the combination of grass and trees in reference to courtyard strategy C (15m x 15m x 15). Strategy C, shows the ability to perform better with vegetation compared to the other two courtyard strategy A (6m x 6m x 6m) and B (15m x 7.5m x 7.5m) which their impacts is not significant because the courtyard in strategy A and B are self-shaded and does not require vegetation to improve its performances. Therefore the study recommended that courtyard with large size can use vegetation as one of the strategy to improve the thermal performance.